Genome-wide characterisation and expression analysis of cellulose synthase genes superfamily under various environmental stresses in Cucumis sativus L. Issue 2 (3rd July 2021) - Sharif, Rahat; Liu, Peng; Wang, Dianwei; Jin, Zhuoshuai; Uzair, Ullah; Yadav, Vivek; Mujtaba, Muhammad; Chen, Peng; Li, Yuhong
ABSTRACT: The cellulose synthase superfamily is comprised of 36 genes in the cucumber genome database. The gene structure and motif analysis revealed that CsCLS genes are highly conserved. The gene ontology (GO) analysis of CsCLS genes unfolded their importance in growth-related and stress-responsive activities. The tissue-specific expression retrieved from RNA-seq data highlighted their importance as most of the CsCLS genes displayed expression in almost all of the tested tissues. Moreover, several genes showed upregulated expression patterns under the botanical fungicide (Chrysophanol and Physcion) treatment. The application of various abiotic (heat, cold, and NaCl stress) and biotic stresses (Powdery and Downy mildew) also stimulated the expression of CsCLS genes. The qRT-PCR analysis of CsCLS genes under gibberellic acid (GA) and melatonin (MT) presented upregulated expression trends in the majority of the genes, giving clues about their involvement in plant development and stress resistance. Furthermore, the transient expression of CsCSLS21 confirmed its location in the cell. Our result provides detailed knowledge of CsCLS genes in cucumber plants. We believe that this information will not only facilitate the development of stress-resilient plants but also improve their total biomass.